2004
DOI: 10.1097/01.mnh.0000133975.32559.6b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of acid-induced bone resorption

Abstract: Purpose of reviewThis review presents our current understanding of the way metabolic acidosis induces calcium efflux from bone, and in the process, buffers additional systemic hydrogen ions associated with acidosis. Recent findingsAcid-induced changes in bone mineral are consistent with a role for bone as a proton buffer. In response to metabolic acidosis in an in-vitro bone organ culture system, we observed a fall in mineral sodium, potassium, carbonate and phosphate, which each buffer protons and in vivo sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(152 citation statements)
references
References 124 publications
(226 reference statements)
5
144
0
3
Order By: Relevance
“…Acidosis has been reported to directly inhibit osteoblast activity, resulting in a reduction in the bone resorbing of minerals and Ca 2+ . 3,70,71 Acidosis may also activate osteoclast activity to increase Ca 2+ release in vitro. 71 Ca 2+ release and mineral dissolution from bone may help systemically buffer protons and restore normal physiological pH.…”
Section: Role For the Ph-sensing Gpcrs In The Skeletal Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Acidosis has been reported to directly inhibit osteoblast activity, resulting in a reduction in the bone resorbing of minerals and Ca 2+ . 3,70,71 Acidosis may also activate osteoclast activity to increase Ca 2+ release in vitro. 71 Ca 2+ release and mineral dissolution from bone may help systemically buffer protons and restore normal physiological pH.…”
Section: Role For the Ph-sensing Gpcrs In The Skeletal Systemmentioning
confidence: 99%
“…Systemic acidosis can occur from respiratory, renal, and metabolic diseases and septic shock. [1][2][3][4]9 Additionally, local acidosis is characterized in ischemic tissues, tumors, and chronically inflamed conditions such as in asthma and arthritis caused by deregulated metabolism and hypoxia. [10][11][12][13][14][15] Acidosis is a stress for the cell.…”
Section: /Clmentioning
confidence: 99%
See 1 more Smart Citation
“…The history of nephrolithiasis is also typical of distal RTA (44). In the presence of metabolic acidosis, the bone serves as an important buffer and exchanges H+ ions for sodium, calcium, and potassium that are complexed to carbonates and phosphates (44). Over time, this leads to increased bone resorption with increased calcium and phosphate release and hypercalciuria with hyperphosphaturia.…”
Section: Question 2amentioning
confidence: 99%
“…However, the use of glucocorticoids leads to a reduction of bone mass due to a direct negative effect on osteoblast activity and to inhibition of osteoclasts, that result in the interruption of the bone remodeling cycle (Dovio et al, 2004). Furthermore, osteoclasts are very sensitive to pH levels as it is known that systemic acidosis has detrimental effects on the skeleton and local acidosis is associated with bone destruction (Arnett, 2003;Krieger et al, 2004;Muzylak et al, 2007). It has been shown that the Ovarian cancer G-protein-coupled Receptor 1 (OGR1 or GPR68), a proton sensing receptor, is essential for osteoclast formation inducing RANKLdependent osteoclastogenesis and activating NFATc1 (Iwai et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%